THE IMPORTANCE OF UNDERSTANDING MEANING TRANSFER IN ONLINE NEWS TEXT A CASE STUDY IN INDONESIAN-ENGLISH TRANSLATION: SEMANTICAL ANALYSIS (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2024)
As news articles are frequently translated or adapted from their original language into different target languages to reach target reader broader, understanding the process of meaning transfer in translation, in some reasons, is crucial for accurate and effective information. This study focused on investigating the phenomenon of meaning transfer in English-Indonesian news texts, specifically focusing on the transition from English to Indonesian through semantical analysis to examine the semantical nuances and challenges encountered when translating news articles. The study aimed at uncovering patterns of meaning transfer and potential discrepancies between the source language and target languages, identifying the strategies used in meaning transfer, examining the challenges faced in conveying meaning across languages, and evaluating the impact of translation decisions on the overall message and tone of the news texts. A case study is implemented to deeply explore the cases faced in translating the text. The data of the study were derived from the Indonesian news article that was translated into English target. The findings of this research shed light on the complexities involved in translating news texts, highlighting the importance of maintaining accuracy, cultural relevance, and readability in the target language. This study, finally, contributes to a deeper understanding of the dynamics of meaning transfer and provides insights that can inform translation practices and enhance the improvement of cross-linguistic communication in news media.